Islam’s Response Towards Modern Science - Selvia Santi (Fakultas Sains dan Teknologi UIN Sunan Kalijaga, 2016)
Modern science was developed by Western since the 16th century and reach its peak in the 20th century through the presence of concrete results of scientific study in various modern technologies. Modern science in technology product and other scientific inventions diffusively spread to many countries. This spread led to encounter between science and Islam. Science as a product from the west were responded differently by Muslim theologician (ulama). This ulama’s attitude categorized into three groups; secular, reconstructive, and semi-conservative. Secular group assume that scientific study as a product of research methods should be accepted as it is. The reconstructives appraising science as a product of western culture that should be reformulated. Whereas the conservatives attempt to match scientific discovery with verses in Al-Qur’an. This grouping based on mindset similarity among the experts who has a tendency to each groups. This study explores the diversity of responses towards modern science that will be the main reference for the experts to develop the thought of science and religion encounter, particularly in Islam.